Change Management: The Contribution of Sustainable Human Resource Management to Organizational Commitment and Employee Innovative Behavior - Rahayu Mardikaningsih (Universitas Nusantara PGRI Kediri, 2024)
Change management is key to improving organizational performance in a changing era. One emerging approach is sustainable Human Resource Management (GHRM), emphasizing environmentally friendly and sustainable practices. This study evaluates the contribution of GHRM to organizational commitment and innovative behavior of employees at four universities in Surabaya. It was conducted with a sample of 25 employees from each college using accidental sampling technique. Data were collected through questionnaires and analyzed by statistical methods. The results show the significance of GHRM contribution to organizational commitment and innovative behavior of employees. GHRM practices that focus on sustainability and environmental friendliness influence employee commitment to college goals and encourage innovative behavior in the workplace. This suggests investment in GHRM strategies is important to create a work environment that motivates, builds commitment, and encourages creativity and innovation, improving organizational performance and competitiveness.